Radional-emotive Counselling and Self-instruction Training for Test Anxious High School Students - Haynes, Christopher R.; Marx, Ronald W.; Martin, Jack; Wallace, Lynn; Merrick, Ruth; Einarson, Tracy (Canadian Journal of Counselling and Psychotherapy, 2011)
This study employed two experiments to determine the relative effectiveness of self-instruction training and rational-emotive counselling in alleviating test anxiety in high school students. In both studies, test anxious grade ten students were assigned randomly to either a rational-emotive counselling group, a self-instruction training group, or a placebo control group. Thirty students participated in Experiment One. Twenty students participated in Experiment Two. Results indicated that both experimental treatments in both experiments were more effective than the placebo control condition in alleviating test anxiety as indicated by scores on the Test Anxiety Inventory (TAI) and the State-Trait Anxiety Inventory (STAI). In Experiment Two, the experimental groups were superior to the control group on both self-report and performance measures (The Canadian Test of Basic Skills - CTBS), and the rational-emotive counselling group was superior to the self-instruction training group on the TAI-W and the CTBS-Reading subscales.